2008
DOI: 10.1053/j.gastro.2007.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial: Lamina Propria Lymphocyte Interactions Promote Epithelial Cell Differentiation

Abstract: Background & Aims-Lymphoepithelial interactions in the gut can occur in the epithelium and the sub-epithelial space. We asked whether Normal, Crohn's Disease (CD) or Ulcerative colitis (UC) lamina propria lymphocytes (LPL) could promote intestinal epithelial cell (IEC) growth and differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 34 publications
(55 reference statements)
3
79
0
Order By: Relevance
“…Similarly, increased phosphorylation of JNK1/2 was seen in inflamed tissue from IBD patients [29,52,53].…”
Section: The Jnk Mapkmentioning
confidence: 80%
“…Similarly, increased phosphorylation of JNK1/2 was seen in inflamed tissue from IBD patients [29,52,53].…”
Section: The Jnk Mapkmentioning
confidence: 80%
“…PI3K activity has been shown to be required for TNF␣-and IL-13-induced claudin-2 expression (15,33). The colonic epithelium of active Crohn disease and ulcerative colitis patients also exhibits higher pERK and pAkt activity, suggesting that activated signaling pathways might be associated with the dysregulation of epithelial function in IBD (38). Our results demonstrated that increased phosphorylation of ERK and Akt is required for the IL-6-mediated claudin-2 expression leading to cation-selective TJ permeability.…”
Section: Discussionmentioning
confidence: 99%
“…(n ϭ 4). plays a critical role in both the transcriptional regulation of intestinal genes, including claudin-2, and the differentiation of intestinal epithelial cells (38). Cdx2 expression is localized only in the epithelial cells at the luminal surface in normal colons, while it occurs also in the colonic crypt in Crohn disease and ulcerative colitis patients (38).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of MAPK-ERK1/2 phosphorylates the downstream proinflammatory proteins such as cytosolic phospholipase A2 and some transcription factors such as activated proteins, Ets-1, Elk and c-myc. Interestingly, ERK1/2, by a study using an ERK1/2 inhibitor, was found to play an important role in the function of immune cells and other cell types during IBD, by regulating some pro-inflammatory mediators [such as interleukin-1 (IL-1)] related signaling transduction [81,82] , evidenced by their enhanced expression and phosphorylation status during IBD [83,84] . Furthermore, the "tightening" junction protein claudin-4, which plays an important role in epithelial barrier function, is regulated by protein kinase ERK [85] .…”
Section: Of Ibdmentioning
confidence: 99%
“…By inducing Akt but blocking p38 signaling, Lactobacillus GG prevents cytokine-induced apoptosis of intestinal epithelial cells, indicating p38 and Akt as key mediators of epithelial barrier function [86,87] . p38 activity is increased significantly in tissues from IBD patients and in mouse models of colitis [83,84,88] , in which inhibition of p38 lowers KC (IL-8) and IL-6 production. A similar result was reported that heatkilled Lactobacillus brevis phosphorylates p38 kinase to regulate the expression of proinflammatory cytokines such as TNF-α, and to improve intestinal integrity [89] .…”
Section: Of Ibdmentioning
confidence: 99%